Faith Integrated Learning and Intelligence: Analyzing the Interaction Effect on Christian Students Mathematics Learning Outcomes - Ering, Aljuanika; Selanno, Semuel; G. Mewengkang, Christie (IJORER : International Journal of Recent Educational Research, 2025)
Objective: This study aimed to examine the interaction effect between instructional strategies and levels of intelligence on students' mathematics learning oucomes at SMP Kristen GMIM Tomohon. The strategies compared included faith-integrated learning and conventional instruction, while students' intelligence levels were categorized as high or low. Method: A quantitative approach with a 2x2 factorial experimental design (treatment by level) was employed. A total of 42 students were assigned to either the experimental (faith-integrated) or control (conventional) group. Data were analyzed using two-way ANOVA with SPSS version 29. Results: The findings revealed a significant interaction between instructional strategies and intelligence levels on mathematics learning oucomes (significance = 0.009 < 0.05). This indicates that instructional effectiveness is influenced by students' intellectual capacities, highlighting the need to align teaching methods with learners' characteristics. Novelty: This study uniquely examines the interaction between faith-integrated instruction and students’ intelligence levels in mathematics learning. It also introduces “thinking in the heart”, a reflective faith-based approach that links mathematical understanding with spiritual values to foster holistic learning.